Successful Treatment of A Catheter-Induced Superior Vena Cava Syndrome through Catheter-Directed Thrombolysis: A Case Report - Reza Ghanavati; Ali Amiri; Nafiseh Ansarinejad; Shokoufeh Hajsadeghi; Hasan Riahi Beni; Seyyed Hashem Sezavar (Journal of Tehran University Heart Center, 2018)
Superior vena cava (SVC) syndrome is a medical condition resulting from the obstruction of the blood flow through the large central veins. Recently, central venous catheters have been reported as the increasingly common cause of this syndrome. We describe a 56-year-old woman with previous history of metastatic colon cancer, who had recently undergone central venous catheter insertion for her second chemotherapy course. Eight days following port insertion, she presented with signs and symptoms suggestive of acute SVC syndrome, which was successfully managed with catheter-directed thrombolysis. The pre-discharge transesophageal echocardiography and conventional angiography showed a patent SVC. The patient was discharged and remained asymptomatic over a 6-month follow-up. This case shows that catheter-directed thrombolysis may be used as a safe treatment for catheter-induced acute SVC syndrome in patients who have undergone catheter insertion in the central vein.